The Urge to Fight: Persistent Escalation by Alcohol and Role of NMDA Receptors in Mice - Covington, Herbert E.; Newman, Emily L.; Tran, Steven; Walton, Lena; Hayek, Walae; Leonard, Michael Z.; DeBold, Joseph F.; Miczek, Klaus A. (Frontiers in Behavioral Neuroscience, 2018)
Alcohol drinking, in some individuals, culminates in pathologically aggressive and violent behaviors. Alcohol can escalate the urge to fight, despite causing disruptions in fighting performance. When orally administered under several dosing conditions the current study examined in a mouse model if repeated alcohol escalates the motivation to fight, the execution of fighting performance, or both. Specifically, seven daily administrations of alcohol (0, 1.8 or 2.2 g/kg) determined if changes in the motivation to initiate aggressive acts occur with, or without, shifts in the severity of fighting behavior. Responding under the control of a fixed interval (FI) schedule for aggression reinforcements across the initial daily sessions indicated the development of tolerance to alcohol’s sedative effect. By day seven, alcohol augmented FI response rates for aggression rewards. While alcohol escalated the motivation to fight, fighting performance remained suppressed across the entire seven days. Augmented FI responding for aggression rewards in response to a low dose of alcohol (1.0 g/kg) proved to be persistent, as we observed sensitized rates of responding for more than a month after alcohol pretreatment. In addition, this sensitization of motivated aggression did not occur with a general enhancement of motor activity. Antagonism of NMDA or AMPA receptors with ketamine, dizocilpine or NBQX during later challenges with alcohol were largely serenic without having any notable impact on the expression of alcohol-escalated rates of FI responding. The current dissociation of appetitive and performance measures indicates that discrete neural mechanisms controlling aggressive arousal can be distinctly sensitized by alcohol.